Neue Familienformen. Herausforderungen für das Recht - Nina Dethloff (Journal of Family Research, 2016)
Family forms are subject to constant change. Apart from the rise in reconstituted families and children growing up in same-sex partnerships, artificial reproduction has led to particular challenges for law. The current legal situation does not correspond to the existing diversity of family forms. The following contribution starts with a brief outline of the societal changes. Subsequently, the legal impact of different family forms will be pointed out. The current legal situation as well as its deficits and options for reform will be analyzed, in particular where the current provisions are under debate. Firstly, the changes resulting from the appearance of new partners as potential new parents will be considered. Secondly, the options for same-sex couples to realize their desire to have children are presented. Thirdly, the focus will be on children conceived through medically assisted reproduction. Here, both the legal consequences of donor insemination as well as the problems resulting from children born by surrogate mothers will be addressed.